Safety and efficacy of aryl‐substituted primary alcohol, aldehyde, acid, ester and acetal derivatives belonging to chemical group 22 when used as flavourings for all animal species - Rychen, Guido (EFSA J, 2017)
Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of 18 compounds belonging to chemical group (CG) 22. They are currently authorised as flavours in food. The FEEDAP Panel concludes that: cinnamaldehyde [05.014] is safe at the maximum use level of 125 mg/kg complete feed for salmonids, veal calves and dogs, and at 25 mg/kg for the remaining target species; cinnamyl alcohol [02.017], 3‐phenylpropan‐1‐ol [02.031], 3‐(p‐cumenyl)‐2‐methylpropionaldehyde [05.045], α‐methylcinnamaldehyde [05.050], 3‐phenylpropanal [05.080], cinnamic acid [08.022], cinnamyl acetate [09.018], cinnamyl butyrate [09.053], 3‐phenylpropyl isobutyrate [09.428], cinnamyl isovalerate [09.459], cinnamyl isobutyrate [09.470], ethyl cinnamate [09.730], methyl cinnamate [09.740] and isopentyl cinnamate [09.742] are safe at the proposed maximum use level of 5 mg/kg complete feed for all target species; 2‐phenylpropanal [05.038], α‐pentylcinnamaldehyde [05.040] and α‐hexylcinnamaldehyde [05.041] are safe at the proposed maximum dose level of 5 mg/kg complete feed for all target species except cats, for which 1 mg/kg is safe. No safety concern would arise for the consumer from the use of these compounds up to the highest proposed level in feeds. Irritation and sensitisation hazards for skin and irritation for eye are recognised for the majority of the compounds under application. Respiratory exposure may also be hazardous. For the majority of the compounds belonging to CG 22, the maximum proposed use levels are considered safe for the environment. For α‐pentylcinnamaldehyde and α‐hexylcinnamaldehyde, a use level up to 0.1 mg/kg feed would not cause a risk for the terrestrial and fresh water compartments. Because all the compounds under assessment are used in food as flavourings and their function in feed is essentially the same as that in food, no further demonstration of efficacy is necessary.